Correction: Multivalent Presentation of MPL by Porous Silicon Microparticles Favors T Helper 1 Polarization Enhancing the Anti-Tumor Efficacy of Doxorubicin Nanoliposomes. - Ismail M Meraz; Claire H Hearnden; Xuewu Liu; Marie Yang; Laura Williams; David J Savage; Jianhua Gu; Jessica R Rhudy; Kenji Yokoi; Ed C Lavelle; Rita E Serda (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0094703.].